Jamaica : Seventh Review Under the Extended Fund Facility and Request for Modification of Performance Criteria-Staff Report; Press Release; and Statement by the Executive Director for Jamaica. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Jamaica's Seventh Review Under the Extended Fund Facility and Request for Modification of Performance Criteria. Risks to the program are slowly waning but remain high. Notwithstanding the authorities' demonstrated resolve in implementing the program, more tangible signs of improvements in growth will be important to sustain the social consensus needed to continue on the reform trajectory. The program is on track. All December 2014 quantitative performance criteria were met and structural reforms have progressed broadly on schedule. Based on the continued strong performance and the authorities' policy commitments, the IMF staff recommends completion of the seventh review.